Transparansi Pengelolaan Dalam Kecendrungan Pilihan Berzakat Ke Lembaga Pengelola Zakat - Abdul Hafiz Sahron (Al-tsaman : Jurnal Ekonomi dan Keuangan Islam, 2020)
Zakat is one of the obligations of Muslims that must be fulfilled, in addition to other obligations. Zakat management organizations that are recognized by the government are the National Amil Zakat Agency (BAZNAS) and the Amil Zakat Institution (LAZ). The Zakat Management Agency must report the results of the management of zakat so that there are no more doubts or worries in the management of zakat funds conducted by BAZNAS and LAZ so as to create transparency in the management of the zakat funds. There are several factors that can influence the choice of tithe in the Zakat Management Institution, namely because of satisfaction factors, namely the quality of service and also transparency in management which includes collection, distribution and utilization of zakat with indicators of management quality and financial reports.